Proceso de atención nutricional en paciente femenino de 45 años de edad con colelitiasis y sobrepeso. - Cabello Villavicencio, Cindy Jomara (2022)
The presence of stones or "stones" in the gallbladder or in the bile ducts is known as gallstones and most people who have this pathology have the stones inside the gallbladder, and it is called cholelithiasis. The present case is based on the study of a 45-year-old female patient who goes to the doctor for pain in the right hypochondrium, is referred to nutritional treatment since she reports having bad eating habits. The objective is to improve her eating style by performing a nutritional assessment according to anthropometric indicators. The nutritional assessment is carried out: Weight: 69 kg, Height: 163 cm. The anthropometric indicator, body mass index (BMI) was used, which resulted in 26.03 kg/m2, according to the WHO the patient is overweight. A conversation was held about her personal history, she does not refer to food allergies. She does not refer to family pathological history. She reports that 8 years ago she underwent surgery (cesarean section). A conversation is held to determine her eating style; He refers not to consuming fruits on a regular basis and that he does not like vegetables, he refers that he eats high-fat foods (fried foods), he refers that he usually gets up at dawn to eat, he refers that instead of water he drinks soft drinks. According to the assessment that was made, the nutritional treatment that this patient will undergo will be a Hypocaloric-Hypofat diet divided into 5 meal times with adequate portions, in addition to drinking plenty of water and performing physical activity.